Relations among psychopathology, substance use, and physical pain experiences in methadone-maintained patients. - Barry, Declan T; Beitel, Mark; Garnet, Brian; Joshi, Dipa; Rosenblum, Andrew; Schottenfeld, Richard S (The Journal of clinical psychiatry, 2009)
Differences in psychiatric distress and substance use (licit and illicit) were examined in methadone maintenance treatment (MMT) patients with a variety of pain experiences.
Keywords: Adult; Chronic Disease; Comorbidity; Connecticut; Female; Humans; Male; Mental Disorders; Methadone; Middle Aged; Opioid-Related Disorders; Pain; Pain Measurement; Personality Disorders; Personality Inventory; Prevalence; Questionnaires; Severity of Illness Index; Somatoform Disorders; Substance Abuse Treatment Centers; Substance-Related Disorders